2016
DOI: 10.1016/j.juro.2016.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncologic Outcomes of Salvage Cryoablation for Radio-Recurrent Prostate Cancer

Abstract: A single center, long-term experience documented by a prospectively maintained database shows that cryoablation is a viable salvage option for radio-recurrent prostate cancer as it provides durable biochemical disease-free survival with acceptable morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
3
10
0
4
Order By: Relevance
“…[27] reported a 5‐year BRFS of 21% applying a PSA nadir of >0.4 ng/mL or every increase of PSA after PSA nadir as the definition of BR. However, using the Phoenix definition 5‐year BRFS rates vary from 45% to 64%, similar to our present data (BRFS of 52%), and resembling BRFS rates reported after salvage prostatectomy [14,20,22,27].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…[27] reported a 5‐year BRFS of 21% applying a PSA nadir of >0.4 ng/mL or every increase of PSA after PSA nadir as the definition of BR. However, using the Phoenix definition 5‐year BRFS rates vary from 45% to 64%, similar to our present data (BRFS of 52%), and resembling BRFS rates reported after salvage prostatectomy [14,20,22,27].…”
Section: Discussionsupporting
confidence: 90%
“…In our present study, the PSA level at initial diagnosis, type of initial treatment, age, interval between initial treatment and SCS, and post‐SCS PSA nadir were significant predictive factors for BRFS. We also confirmed that patients with a pre‐SCS PSA level of >10 ng/mL have worse outcomes than those with a PSA level of <10 ng/mL [14,19,20]. This finding emphasises the importance of early recognition of patients with rrPCa.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations